Overweight/obesity risks and prevalence of diabetes and hypertension in North Eastern India: An analysis using seemingly unrelated probit model - Strong P. Marbaniang; Hemkhothang Lhungdim; Brijesh Yadav; Vinit Kumar Yajurvedi (Elsevier, 2021)
Objective: It would be reasonable to hypothesize that common unobserved factors, such as psychological stress and anxiety, as well as genetic and environmental factors, simultaneously influence the tendency for overweight or obesity and the prevalence of chronic disease. The paper tries to examine the joint influence of an individual's and socio-economic characteristics in determining overweight or obesity and chronic disease. Methods: The sample comprised of 112,062 male and female participants age 15-49 years. For the simultaneous joint estimation approach we employ a seemingly unrelated probit model with and without control for endogeneity. Results: The non-zero correlation coefficient obtained from the analysis reveals that overweight or obesity is related to diabetes and hypertensions, indicating the existence of unmeasurable individual factors that commonly affect the propensity to diabetes and hypertension and overweight or obesity. A 10% increase in overweight and obesity causes increment of 4% in diabetes, 4.9% in hypertension. Further, among the overweight or obese individual, a 10% increase in overweight and obesity causes increment of 4.7% in diabetes, and 6.5% in hypertension in the study area. Conclusion: The study indicates presence of unobserved factors that simultaneously affect overweight/obesity and prevalence of both diabetes and hypertension. Policy and health promotion programme should also give special attention to the unmeasurable factors (for example: genetic factors, psychological stress and long working hour) that commonly influence the risk of overweight or obesity and chronic diseases.